2019
DOI: 10.31234/osf.io/w6j4a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Foreground Bias: Differing impacts across depth on visual search in scenes

Abstract: When you walk into a room, you perceive visual information that is both close to you and farther in depth. In the current study, we investigated how visual search is affected by information across scene depth and contrasted it with the effect of semantic scene context. Across two experiments, participants performed search for target objects appearing either in the foreground or background regions within scenes that were either normally configured or had semantically mismatched foreground and background context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…For instance, Mazza et al (2005) found in a change-detection task that changes were detected more quickly in the scene foreground than the scene background. More recently, we found that during visual search, target objects were found faster when they were located in the foreground than in the background (even when object size was controlled; Man et al, 2019). Together, these studies suggest that prioritizing the foreground may continue to exert influence in later processing, but further research is needed to delineate its extent.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Mazza et al (2005) found in a change-detection task that changes were detected more quickly in the scene foreground than the scene background. More recently, we found that during visual search, target objects were found faster when they were located in the foreground than in the background (even when object size was controlled; Man et al, 2019). Together, these studies suggest that prioritizing the foreground may continue to exert influence in later processing, but further research is needed to delineate its extent.…”
Section: Discussionmentioning
confidence: 97%
“…In the absence of a perceptual task (e.g., visual search), our attentional resources are preferentially allocated to the identification of objects within our peripersonal space -that is, the region immediately surrounding the perceiver, typically within an arm's reach (for a review, see Castelhano & Krzyś, 2020). As a result, objects within peripersonal space are identified more accurately (Fernandes & Castelhano, 2019;Josephs & Konkle, 2019;Man, Krzys, & Castelhano, 2019). This prioritization of information closer to the perceiver is also known as the "foreground bias."…”
Section: Object Recognition Depends On Attentionmentioning
confidence: 99%
“…In recent years, interest has grown in how information processing across depth impacts attention and memory of scene representations (Bonner & Epstein, , 2018Josephs & Konkle, 2019;Man et al, 2019). Traditionally, studies of depth perception have examined observers' estimates of distance (Cutting & Vishton, 1995;Nagata, 1991) and how information at different distances is processed: from peripersonal to vista space (Costantini et al, 2011;Cutting & Vishton, 1995;Previc, 1998).…”
Section: Spatial Processing Across Depth and Attentional Processesmentioning
confidence: 99%
“…Recent studies on scene processing have also shown qualitatively different processing of spaces closer to the observer (Bonner & Epstein, 2017, 2018Fernandes & Castelhano, 2021;Josephs & Konkle, 2019;Man et al, 2019). Most recently, Castelhano and Fernandes (2021) found a foreground bias when examining rapid scene perception for images that had mismatched scene categories in the foreground and background (i.e., chimera scenes).…”
Section: Spatial Processing Across Depth and Attentional Processesmentioning
confidence: 99%
See 1 more Smart Citation